2019
DOI: 10.1017/s0143814x19000138
|View full text |Cite
|
Sign up to set email alerts
|

It could happen to you: how perceptions of personal risk shape support for social welfare policy in the American States

Abstract: Is public support for social welfare programs’ contingent on an individual’s exposure to risk? Prior work has examined whether tough economic times lead people to “reach out” (i.e. become more accepting of government expansion of social welfare programs) or “pull back” (i.e. become less supportive of welfare). However, these studies do not account for the conditional relationship between an individual’s exposure to risk and his or her risk orientation. Using new survey data, we find that an individual’s risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…This prediction is similar to what many studies have found: namely, that economic insecurity leads to support for left-wing policies (Cusack et al, 2006; Rehm et al, 2012; Rehm, 2011; Milita et al, 2019; Vlandas, 2019). Sharp increases in financial market risk, in this view, can serve to reduce electoral support for parties with a traditional right-wing profile, thereby generating cycles in patrimonial voting over time.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…This prediction is similar to what many studies have found: namely, that economic insecurity leads to support for left-wing policies (Cusack et al, 2006; Rehm et al, 2012; Rehm, 2011; Milita et al, 2019; Vlandas, 2019). Sharp increases in financial market risk, in this view, can serve to reduce electoral support for parties with a traditional right-wing profile, thereby generating cycles in patrimonial voting over time.…”
Section: Introductionsupporting
confidence: 90%
“…Against this background and given the long tradition of research on the relationship between economic vulnerability and opinions on economic policy (e.g., Cusack et al, 2006; Helgason & Mérola, 2017; Milita et al, 2019; Rehm et al, 2012; Vlandas, 2019), we would expect extensive research on how changes in financial market risk affect both policy attitudes and voting behavior. Surprisingly, however, little work has been found to be done in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk-neutrals were the respondents scoring 4. We recoded this variable, as done elsewhere (Milita et al, 2019), so that lower scoring equals greater RAC (3 = 1; 2 = 2 and 1 = 3) and higher scores equals greater RAV (7 = 1; 6 = 2 and 5 = 3). RAC ranges from 1 to 3, with higher values denoting greater risk acceptance and '0' denoting that respondent is either risk-averse or risk-neutral.…”
Section: Data Measurementmentioning
confidence: 99%
“…However, risk orientation influences public opinion and preferences for public programs, in general, and for health programs, in particular, remains to be studied. A recent study found that the support for welfare spending was rooted in the individuals' perception of risk exposure conditional on their propensity to tolerate that risk (Milita et al, 2019). In the context of healthcare rationing decisions, the influence of the personality trait of risk orientation is unknown.…”
Section: Introductionmentioning
confidence: 99%